Concrete mathematics : a foundation for compouter science, 2nd edition - Graham Ronald L., Knuth Donald E. & Patashnik Oreh (Dorling kindsley, Delhi, 2009)
Stats/Maths
UGC XIth Five Year Plan 2009-2010
ENGLISH
Keywords: Concrete mathematics : a foundation for compouter science, 2nd edition; Stats/Maths; Stats/Maths